2018
DOI: 10.1088/1555-6611/aa9d6d
|View full text |Cite
|
Sign up to set email alerts
|

Classifying low-grade and high-grade bladder cancer using label-free serum surface-enhanced Raman spectroscopy and support vector machine

Abstract: This study aims to classify low-grade and high-grade bladder cancer (BC) patients using serum surface-enhanced Raman scattering (SERS) spectra and support vector machine (SVM) algorithms. Serum SERS spectra are acquired from 88 serum samples with silver nanoparticles as the SERS-active substrate. Diagnostic accuracies of 96.4% and 95.4% are obtained when differentiating the serum SERS spectra of all BC patients versus normal subjects and lowgrade versus high-grade BC patients, respectively, with optimal SVM cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…Meanwhile, the mentioned methods are costly and time-consuming in spite of their high precision. Finally, although the SVM method has been used as an appropriate and valid algorithm for identifying effective factors in different studies (Chang et al, 2003;Jumutc et al, 2011;Wang, 2005;Zhang et al, 2018), it still has several advantages and disadvantages (Abe, 2005;Guyon et al, 2002;Yoo et al, 2012). One of the most important advantages of SVM, as a classification method, is the improvement of efficiency with the increase of data dimension.…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, the mentioned methods are costly and time-consuming in spite of their high precision. Finally, although the SVM method has been used as an appropriate and valid algorithm for identifying effective factors in different studies (Chang et al, 2003;Jumutc et al, 2011;Wang, 2005;Zhang et al, 2018), it still has several advantages and disadvantages (Abe, 2005;Guyon et al, 2002;Yoo et al, 2012). One of the most important advantages of SVM, as a classification method, is the improvement of efficiency with the increase of data dimension.…”
Section: Resultsmentioning
confidence: 99%
“…The potential of SERS spectroscopy for discrimination of high-grade and low-grade bladder cancer cells was demonstrated. 47 49 The possibility to predict the bladder cancer grade by SERS analysis of urine supernatant and sediment was proposed. 47 Recently, a new elegant NIR-SERS platform based on modified Au–Ag nanohollows was developed for effective discrimination of high-grade and low-grade bladder cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…The SERS technique overcomes the low inherent sensitivity of ordinary Raman spectroscopy. Several groups have demonstrated the promising advantages of the SERS approach in analysis of bladder cancer. The first attempts to employ SERS spectroscopy for the analysis of the cultured bladder cancer cells are described by Jin et al in 2015. Following studies have shown that in vivo imaging of the bladder tissue can be performed using SERS nanotags or that the noninvasive and muscle-invasive bladder cancer cells can be determined from liquid biopsies .…”
Section: Introductionmentioning
confidence: 99%
“…Biomarker detection is the most effective strategy to improve the prognosis of patients with nasopharyngeal carcinoma (NPC); therefore, the development of point-of-care test with high sensitivity and specificity for tracking NPC progression is critical for disease management. Raman spectroscopy has been developed as an outstanding vibrational spectroscopy technique for multiplexed molecular analysis 1 , 2 . This exclusive feature offers the potential for progression evaluation.…”
Section: Introductionmentioning
confidence: 99%